RAILWAY STRUCTURES PERFORMANCE DUE TO FREIGHT INTERMODAL SERVICE AT BOJONEGORO – KALITIDU ROUTE - Nugroho Utomo (CI-TECH, 2021)
Goods movement using container are quite efficiently assessed because it can carry a great amount of goods fit to container capacity. Freight transportations is a primary component of all supply-chain and logistics systems, but in contrary using a truck as its transportation means causing many problems such as air and noise pollutions, traffic congestions, road accidents and road damage. Depart from this facts, so government is looking for another means of freight transporter which more efficient with a bigger load capacity advantages. This options goes to train as a solutions of intermodal freight transportations lack. In order to supporting intermodal freight transportations, right now double track of railway is available for Jakarta – Surabaya route (Northern line route). By now, noted that freight transportation with double track railway frequency is potentially increase to 15 trip per days with capacity 500 TEU (Twenty feet Equivalent Units) per days and fuel consumptions (with truck) can be thrifted into 115 kl per days also reducing carbon monoxide emission amounts 350 tons per days. According with an official statements from Directorate General of Railways, Ministry of Transportations, explained that Jakarta – Bojonegoro route on double track railway is fully operated so this paper is conducted to determining feasibility of railway structure performance due to freight intermodal transportations at Bojonegoro – Kalitidu route. Railway structure performance feasibility is observed from loading distributions, rail strength, rail sleeper strength, and railway subgrade endurance to planned freight trains. As a result of this research obtained that tension force that occurred on rail is 830,10 kg/cm2 < permitted tension on rail (first class rail) 1325 kg/cm2. So, tension force that occurred on rail is safe. Moment force that occurred on rail bottom is 14521,25 kg.cm < permitted moment force (150.000 kg.cm) Moment force that occurred in the middle of rail sleeper is 58993,978 kg.cm < permitted moment force (93000 kg.cm). Tension force that occurred on above railway subgrade (σ2) is 4,17 kg/cm2 < qu (29,671 kg/cm2). It means that railway subgrade is capable to supporting load of freight transportation operations along Bojonegoro – Kalitidu route.